REFUSAL STRATEGIES AND POLITENESS IN VIRTUAL COMMUNICATION: A CYBERPRAGMATICS STUDY - Dinda Noor Azizah; Dadang Sudana (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
This study aims to investigate the use of speech act refusal strategies in virtual communication via instant message application, WhatsApp. This study uses cyberpragmatics and relative relations studies to determine the form of a politeness strategy for the participants who are involved in virtual communication. The object studied are screenshots of the WhatsApp chat between a banker and a prospective bank customer which is analyzed by using a qualitative descriptive and Discourse Completion Task (DCT) methods. The results showed that the dominant refusal strategy that emerged was the indirect refusal strategy, which included reason, statement of regret, and promise of future acceptance. Also, the use of negative politeness has a more tendency towards the use of refusal strategies.